IMPLEMENTASI TRI HITA KARANA DALAM PENGELOLAAN HUTAN ADAT DI DESA DEMULIH, BANGLI - Ni Luh Putu Mahendra Dewi; Dewi Maria Oktaviana Yulti; Ida Ayu Anggara Sri Anjani; Ni Made Setiani (Jurnal Ecocentrism, 2026)
The Tri Hita Karana philosophy encompasses the relationship between humans and God (parhyangan), between humans (pawongan), and between humans and the environment (palemahan). The study aims to determine the application of Tri Hita Karana in the management of customary forests in Demulih Village. Information was obtained through interviews with customary forest managers and direct observation. The implementation of Tri Hita Karana in the parhyangan aspect is reflected in the piodalan activities held by the Demulih customary forest management community in eleven temples within the customary forest area and there are pools for melukat activities that are open to the entire community accompanied by customary forest managers. In the pawongan aspect, the determination of customary forests is managed by the Demulih Customary Law Community (Customary Village) as the guardian of customary forests, the utilization of customary forests with production functions and the management of customary forests are regulated in awig-awig, including the prohibition of entering forest areas during the mourning period which lasts for 12 days. The Palemahan aspect is reflected in the activities of Customary Forest Stakeholders in managing Customary Forests, utilizing traditional knowledge in the utilization of genetic resources, non-timber forest products, and environmental services, as well as protecting against forest and land fires. Therefore, this research is expected to provide a source of information regarding the implementation of Tri Hita Karana in customary forest areas in Bali.